The making of Terra: gameplay and level design - Koh, Boon Xuan (Nanyang Technological University, 2024)
“Terra: New Horizons” consists of a 3D cinematic trailer and game set on Planet Terra in the far future, where living conditions on other planets have been ruled unsustainable. The team comprises of Ben Lee Kuan Yong, Koh Boon Xuan, and Ryan Christian Misson. This document serves to provide an insight to the development of “Terra: New Horizons.”